Effectiveness Of Comprehensive Rehabilitation Nursing for Patients after Laparoscopic Myomectomy. Literature Review - Gulbinaitė, Laura (Slauga. Mokslas ir praktika, 2025)
The aim. To review scientific literature on the effectiveness of comprehensive rehabilitation nursing for patients after laparoscopic myomectomy. Methods. A literature review was conducted in the PubMed database by using advanced search. Literature search was conducted in English according to the following keywords and their combinations: laparoscopic myomectomy, laparoscopic myomectomy nursing, uterine fibroids nursing, nursing after uterine fibroids surgery, postoperative comprehensive rehabilitation nursing. A total of 242 publications in English were found in the database. Articles were selected based on three criteria: the title, the abstract, and the full text. Six scientific articles published between 2019 and 2024 were selected and thoroughly analyzed. Descriptive analysis was conducted. Results. The results of the publications were analyzed according to the type of application of comprehensive nursing methodologies. Comprehensive rehabilitation nursing encompasses a holistic approach, integrating medication management, nutrition, physical activity, and psychological support. Studies show that patients receiving comprehensive nursing care experience shorter recovery times, reduced complications, and improved satisfaction compared to those receiving standard nursing care. Summary. Comprehensive rehabilitation nursing, implemented through complex and humanized nursing methodologies, is effective for patients post-laparoscopic myomectomy as it reduces the physical and psychological stress which patients undergo, increases the patient satisfaction, shortens hospitalization duration, decreases the incidence of related complications, and improves the patients’ quality of life, thereby accelerating recovery after surgery. Therefore, this strategy is worth applying in clinical practice. The results of this literature review provide valuable perspectives for future research in the field of nursing for patients after laparoscopic surgery.
Keywords: nursing after laparoscopic myomectomy